Synthesis and characterization of a novel series of benzenesulfonylurea and thiourea derivatives of 2H-pyran and 2H-pyridine-2-ones as antibacterial, antimycobacterial and antifungal agents - Faidallah, Hassan Mostafa; Khan, Khalid Ali; Asiri, Abdullah Mohammad (European Journal of Chemistry, 2011)
Arylhydrazines reacted with dehydroacetic acid (1) to give the corresponding 2H-pyran-2-one hydrazones (2), which on treatment with hydrazine hydrate afforded the corresponding 1-amino-2H-pyridin-2-ones (3). Reaction of 3 with nitrous acid, aromatic aldehyde and substituted benzenesulfonyl chlorides yielded the corresponding 2H-pyridine-2-one derivatives. A series of urea and thiourea derivatives were also prepared. Some of these compounds have shown significant antibacterial and mild to moderate antimycobacterial and antifungal activities.